‘Tell me what he said! We’ll decide if it makes sense or not’: a case study of legal interpreting between English and Chinese in Britain - Leung, Ester S.M. (International Journal of Speech, Language and the Law, 2001)
The principle that, during police interviews, people who do not speak English should have access to interpreters has long been established in legal practice in the UK. However, very little is known about the extent to which or how this principle is actually applied. The aim of this study was to provide a close look at current legal interpreting practices in different types of legal encounter in the UK. The broad questions guiding my analysis were: what was actually going on in these events; what were the specific problems associated with interpreting in legal settings; and what were the problems associated with interpreting between Cantonese and English? What can the close study of interpreters as they interpret tell us about the process of ‘interpretation’ in legal settings? An ethnographic approach was adopted to collect and analyse the data. I observed and audio-recorded four interpreting events which involved Chinese interpreters. In order to understand the process of interpretation and reflect the interpreter’s point of view, interviews with each interpreter involved were arranged immediately after the recorded data has been transcribed. The main finding emerging from this study is that the legal practitioners exerted most control over the interaction through their use of language. However, this control was sometimes undermined, knowingly or unwittingly, by both interpreters and clients. In addition, it was found that, while interpreting, the interpreters were trying to understand what was said, but that their understanding was shaped by their knowledge and experience of the world. The interpreters in my study filtered information which they deemed to be significant and relevant to the situation. Working with different languages and with different cultural traditions, the interpreters could only interpret in ways which they thought were most appropriate to the situation. For example in one interview, the police needed to find out whether the suspect had bought an MOT certificate knowing that purchase of the certificate was illegal. Since time of the action was not marked in the suspect’s answers (because in Chinese the verb itself does not indicate time); the interpreter clarified with the suspect, on her own initiative, whether he knew at the moment he bought the certificate that the purchase would constitute a crime. Interpreters were making moment-by-moment decisions related to the unfolding of the interpreting event rather than by reference to established procedures. Because of the complexity of the interactional processes and the power asymmetries involved in events such as these, I argue for a more dialogic approach to the study of legal interpreting, one which takes account of the participants’ understanding of particular legal interpreting events. I also argue for a more critical approach to the study of legal interpreting, one which takes full account of the wider institutional and discursive context in which specific legal interpreters find themselves working.